Capture of tobacco use among population‐based registries: Findings from 10 National Program of Cancer Registries states. Issue 11 (26th March 2018) - Siegel, David A.; Henley, S. Jane; Wike, Jennifer M.; Ryerson, A. Blythe; Johnson, Christopher J.; Rees, Judy R.; Pollack, Lori A.
Abstract : BACKGROUND: Tobacco use data are important when the epidemiology and prognosis of tobacco‐associated cancers are being defined. Central cancer registries in 10 National Program of Cancer Registries states pilot‐tested the collection of standardized tobacco use variables. This study evaluated the capture of tobacco use data and examined smoking prevalence among cancer patients. METHODS: Participating registries collected data about the use of tobacco—cigarettes, other smoked tobacco, and smokeless tobacco—for cases diagnosed during 2011‐2013. The percentage of cases with known tobacco variable values was calculated, and the prevalence of tobacco use was analyzed by the primary cancer site and state. RESULTS: Among 1, 646, 505 incident cancer cases, 51% had known cigarette use data: 18% were current users, 31% were former users, and 51% reported never using. The percentage of cases with a known status for both other smoked tobacco and smokeless tobacco was 43%, with 97% and 98% coded as never users, respectively. The percent known for cigarette use ranged from 27% to 81% by state and improved from 47% in 2011 to 59% in 2013 for all 10 states combined. The percent known for cigarette use and the prevalence of ever smoking cigarettes were highest for laryngeal cancer and tracheal, lung, and bronchus cancer. CONCLUSIONS: Cancer registrars ascertained cigarette use for slightly more than half of all new cancer cases, but other tobacco‐related fields were less complete. Studies to evaluate the validity of specific tobacco‐related variables and the ability of cancer registries to capture this information from the medical record are needed to gauge the usefulness of collecting these variables through cancer surveillance systems. Cancer 2018;124:2381‐9 . © 2018 American Cancer Society . Abstract : The Centers for Disease Control and Prevention has piloted cancer registry variables to capture tobacco use at cancer diagnosis. This article evaluates cancer registry variable completeness and analyzes the prevalence of tobacco use by primary cancer site and state.